Progress in S–X Bond Formation by Halogen-Mediated Electrochemical Reactions - Du, Juan; Du, Ya-long; Gui, Qing-wen (Synthesis, 2023)
Sulfur-containing compounds are very common and important heteroatom skeletons and are widely found in natural products, pharmaceuticals and bioactive compounds. Moreover, the development of synthetic routes to organosulfur compounds has attracted considerable attention due to their wide range of applications in organic chemistry, the pharmaceutical industry and in materials science. As one of most powerful, green and eco-friendly research areas, organic electrosynthesis, in contrast to conventional organic synthesis, can avoid the use of harmful stoichiometric external oxidants or reductants. Importantly, halide salts are widely used as supporting electrolytes and redox catalysts in indirect electrosynthesis to avoid the limitations imposed by high overpotentials in direct electrosynthesis. In recent years, significant progress has been made on the halogen-mediated electrosynthesis of organosulfur compounds. In this review, the scope, limitations and mechanisms of halogen-mediated electrochemical transformations of sulfur-containing compounds are presented and discussed.1 Introduction2 S–C Bond Formation2.1 Organic Thiocyanates2.2 Sulfonyl Compounds2.3 Other Sulfides3 Formation of Other S–X (X = N, O, S, P) Bonds4 Conclusion and Outlook
Keywords: organosulfur compounds; electrosynthesis; halogen-mediated; eco-friendly; sulfonyl compounds; organic thiocyanates